2019
DOI: 10.3390/brainsci9050123
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Non-Gaussian Diffusion Metrics in Chronic Disorders of Consciousness

Abstract: Diagnostic accuracy of different chronic disorders of consciousness (DOC) can be affected by the false negative errors in up to 40% cases. In the present study, we aimed to investigate the feasibility of a non-Gaussian diffusion approach in chronic DOC and to estimate a sensitivity of diffusion kurtosis imaging (DKI) metrics for the differentiation of vegetative state/unresponsive wakefulness syndrome (VS/UWS) and minimally conscious state (MCS) from a healthy brain state. We acquired diffusion MRI data from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Moreover, the brainstem‐hypothalamus, brainstem‐temporal lobe, and thalamus‐temporal lobe connectivity have also been reported to be involved in the recovery of impaired consciousness 1 . In another study, metrics for gray and white matter were revealed to be reduced in many regions including the brainstem in patients with DOC 22 . The possibility of differentiating between the VS and the MCS was demonstrated by evaluating the total score of the brainstem and/or thalamus degeneration from the DOC‐MRI‐based Distinguishing Scale criteria 2 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the brainstem‐hypothalamus, brainstem‐temporal lobe, and thalamus‐temporal lobe connectivity have also been reported to be involved in the recovery of impaired consciousness 1 . In another study, metrics for gray and white matter were revealed to be reduced in many regions including the brainstem in patients with DOC 22 . The possibility of differentiating between the VS and the MCS was demonstrated by evaluating the total score of the brainstem and/or thalamus degeneration from the DOC‐MRI‐based Distinguishing Scale criteria 2 .…”
Section: Discussionmentioning
confidence: 96%
“…1 In another study, metrics for gray and white matter were revealed to be reduced in many regions including the brainstem in patients with DOC. 22 The possibility of differentiating between the VS and the MCS was demonstrated by evaluating the total score of the brainstem and/or thalamus degeneration from the DOC-MRI-based Distinguishing Scale criteria. 2 The results of these studies suggest that the brainstem may function as one of the hubs in the brain that connect the network of consciousness.…”
Section: Relationship Between the Brainstem Features And Consciousnes...mentioning
confidence: 99%
“…The brain's global properties are explored, for example, in [42]. It has become possible to record the activity of huge populations of neurons and individual cells [43]. Since new tomographs can record blood flows in the brain, it will be possible to determine the circulation of neuron messages indirectly using these methods.…”
Section: Discussionmentioning
confidence: 99%
“…1 for details). This amount, although high (∼37%), presents no deviation from the common exclusion criteria in the area of research on patients with severe brain injuries (Cao et al 2019;Pistoia et al 2014;Kremneva et al 2019;Forgacs et al 2017). Finally, the analysis included a set of 86 measurements from 60 PDOC patients (N = 53, including 20 females, aged 36.88 ± 13.53, see Tab.…”
Section: Subjectsmentioning
confidence: 99%